A preliminary study on the collaborative use of statistical modeling in a GIS study of asthmatic morbidity / Mohammad Said Zainol, Sayed Jamaludin S. Ali and Zainal Mat Saat - Zainol, Mohammad Said; S. Ali, Sayed Jamaludin; Mat Saat, Zainal (Fakulti Teknologi Maklumat dan Sains Kuantitatif, 2005)
This paper reports an ongoing effort in the collaborative use of statistical modeling techniques and GIS in an epidemiological related research. The problems of increasing asthmatic prevalence and morbidity and their relationship to environmental pollutants in the state of Perlis are being investigated. The main hypothesis is that asthmatic prevalence and morbidity increases where and when levels of specific air pollutants increase. The widely common conjecture that exposure to air pollutants has adverse effects upon respiratory diseases, particularly asthma, is translated into a belief that air pollutants correlate with asthmatic prevalence and morbidity, which in turn calls for the construction of models of statistical relationships between levels of air pollutants and asthmatic prevalence. Outputs of this model provide an interesting dimension to the use of GIS technology in the research into asthmatic morbidity and prevalence.